Parental Communication on Sexual Health: An Integrative Review of Educational Content and Topics - Fitri Fujiana; Yati Afiyanti; Imami Nur Rachmawati; Aria Kekalih (Journal of Health and Nutrition Research, 2026)
Parents play an important role in their children's sexual health education. The purpose of this study was to examine the materials or topics that parentsconvey when providing sexual health education to their children. The study design was an integrative review using the PRISMA flow diagram withthe CoCoPop framework. The databases used were Cochrane, Scopus, and EBSCO Medline. The inclusion criteria for articles were: abstract andfull text, qualitative, quantitative, and mixed- method research journal articles, English language, published between 2020 and 2024, and a population of parents with children aged 0 to 18 years. The JBI tool was used to evaluate the articles. The results of the study found nine articles, including three quantitative articles, four qualitative articles, and two mixed-method articles. The conclusion of this integrative review is that eachparent conveys different topics or materials, depending on the knowledge, abilities, and stigma of the parents and children regarding sex education. The materials most frequently discussed by parents were puberty, safe touching, unsafe pregnancy and abortion, premarital sex, contraception, sexually transmitted infections, reproductive anatomy, and protection from sexual violence. The recommendation from this study is that there is a need for clear guidelines on age- appropriate sexual health education that can be used by parents from various backgrounds.